Cross-Talk between Ionic and Nanoribbon Current Signals in Graphene Nanoribbon-Nanopore Sensors for Single Molecule Detection - Puster, Matthew (Small, 2015)
Nanopores are now being used not only as an ionic current sensor but also as a means to localize molecules near alternative sensors with higher sensitivity and/or selectivity. One example is a solid-state nanopore embedded in a graphene nanoribbon (GNR) transistor. Such a device possesses the high conductivity needed for higher bandwidth measurements and, because of its single-atomic-layer thickness, could improve the spatial resolution of the measurement. Here we show two-channel measurements of ionic current through the nanopore during double-stranded DNA (dsDNA) translocation, along with the simultaneous response of the neighboring GNR due to changes in the surrounding electric potential. We observe cross-talk originating from capacitive coupling between the two measurement channels, resulting in a transient response in the GNR during DNA translocation; however, we do not observe a modulation in device conductivity via an electric field effect response, due to changes in local solution potential during DNA translocation. A field effect response would scale with GNR source-drain voltage (V(ds)), whereas the capacitive coupling does not scale with V(ds). In order to take advantage of the high bandwidth potential of such sensors, the field effect response must be enhanced. We present potential field calculations to outline a phase diagram for detection within the device parameter space, charting a roadmap for future optimization of such devices.